Detail Process Charting : Speaking the Language of Process - Graham, Ben B. (Hoboken, New Jercy John Wiley & Sons, 2004)
Praise for Detail Process Charting''A must-read for any competitive organization, Detail Process Charting: Speaking the Language of Process provides a comprehensive, yet clear, explanation of how to utilize one of the most powerful tools available to improve work processes.
Include Index and Illustration
Keywords: IndustrialOrganization -- Organization Charts -- Organizational Effectiveness